ASAS PEMISAHAN HORIZONTAL (HORIZONTALE SCHEIDING BEGINSEL) DAN ASAS PERLEKATAN (VERTICALE ACCESSIE) DALAM HUKUM AGRARIA NASIONAL - Sri Harini Dwiyatmi (Refleksi Hukum: Jurnal Ilmu Hukum, 2020)
The National Land Law, regulated in Law No. 5 of 1960 concerning Basic Regulations on Agrarian Principles, was formed from the Indonesian customary law as the original character of the Indonesian people. From 1960, the principles in the national customary law, which are suitable with the Indonesian features, have contributed to the National Land Law development. One of its Principles is the Principle of Horizontal Separation. This Principle is not absolute as the Principle of vertical accesssie may be applied as well. This research observed the application of the Principle of Horizontal Separation and the Principle of vertical accessie in the National Land Law.